Endoscopic sleeve gastroplasty: a modified technique with greater curvature compression sutures - Glaysher, Michael A.; Moekotte, Alma L.; Kelly, Jamie (Endoscopy International Open, 2019)
Background Endoscopic sleeve gastroplasty (ESG) is rapidly becoming established as a safe and effective means of achieving substantial weight loss via the transoral route. New ESG suture patterns are emerging. Our aim was to investigate whether superior weight loss outcomes can be achieved by using a unique combination of longitudinal compression sutures and “U”-shaped sutures.Methods This is a retrospective review of prospectively collected data of all patients undergoing ESG by a single operator in a single UK center.Results Between January 2016 and December 2017, 32 patients (23 female) underwent ESG; n = 9 cases were completed utilizing a commonly used triangular suture pattern (“no longitudinal compression”) and n = 23 cases were completed using our unique “longitudinal compression” suture pattern. In the no compression and compression groups, the mean ages were 45 ± 12 years and 43 ± 10 years, the median baseline weights were 113.6 kg (range 82.0 – 156.4) and 107 kg (range 74.0 – 136.0), and the median baseline body mass indexes (BMIs) were 35.9 kg/m2 (range 30.9 – 43.8) and 36.5 kg/m2 (range 29.8 – 42.9), respectively. After 6 months, body weight had decreased by 21.1 kg (range, 12.2 – 34.0) in the compression group (n = 7) versus 10.8 kg (range, 7.0 – 25.8) in the no compression group (n = 5) (P = 0.042). Correspondingly, BMI decreased by 7.8 kg/m2 (range, 4.9 – 11.2) and 4.1 kg/m2 (range, 2.6 – 7.2) in each group, respectively (P = 0.019). Total body weight loss (%TBWL) was greater in the compression group at 19.5 % (range, 12.9 – 30.4 %) compared to 13.2 % (range, 6.2 – 17.1 %) in the non-compression group (P = 0.042). No significant adverse events were reported in this series.Conclusion The technique of ESG is evolving and outcomes from endoscopic bariatric therapies continue to improve. We provide preliminary evidence of superior weight loss achieved through a modified gastroplasty suture pattern.